Arbuscular mycorrhizal fungi inf luence on growth and development of Capsicum annuum L. - Alonso-Contreras, Rogelio; Aguilera-Gómez Luis Isaac; Rubí-Arriaga Martín; González-Huerta Andrés; Olalde-Potugal, Victor; Rivas-Manzano, Irma Victoria (Revista Mexicana de Ciencias Agrícolas, 2018)
This research was conducted to determine the density, diversity and dynamics of arbuscular mycorrhizal fungal spores (HMA) on the ground under and outside the canopy of an orchard of apple (Malus domestica Borkh.) of the municipality of San Felipe del Progreso, State of Mexico. A trial was conducted in a greenhouse with Capsicum annuum L., to evaluate the influence of AMF in the absorption of phosphorus (P) the trial was conducted in a 3x2 factorial design with eight replications, under a completely randomized design. We evaluated plant height, stem diameter, number of leaves, leaf area, dry weight of the aerial part of the plant and root dry weight. The results obtained in 100g of soil helped to identify 570 and 481 AMF spores down out of the tree, respectively. We also found that, the guild of HMA in the garden consisted of: Glomus coremioides, G. Sinuosum, G. geosporum and Gigaspora sp. The results of the test under greenhouse indicated that, the AMF had a positive effect (p> 0.05) on stem diameter, leaf area, dry weight of shoot and root dry weight, when acting simultaneously with 22 μg ml-1 of P. In root dry weight, mycorrhizal treatment-22 μg ml -1 of P and mycorrhizal interaction of P dose did significantly influenced.